Optimalisasi Aset Desa: Pendampingan Kepada Pemerintah Desa Tanjung Lago - Taufik Raharjo; M. Taufik Hidayat; Cyntya Simamora (Asosiasi Dosen Akuntansi Indonesia, 2020)
This community service is motivated by the many assets of Tanjung Lago Village that have been built by the Village Government through the Village Fund but have not functioned optimally for the village community. Tanjung Lago Village is one of the oldest villages located in Talang Kelapa District, Banyuasin Regency, South Sumatra. This service aims to help Tanjung Lago Village officials in making the concept of a tourist village by utilizing existing village assets. This activity is carried out in three stages, namely analysis of the protection of village assets, making the concept of optimizing village assets, and presentation of concepts. Analysis of the potential of village assets using the SWOT analysis approach. The result of this activity is the concept of optimizing the assets of Tanjung Lago village towards a tourist village.